Asuhan Keperawatan Pada Ny. S Dengan Post Operasi Sectio Caesarea Indikasi Riwayat Sectio Caesarea Di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Delti Srimiyati; Tati Karyawati (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Sectio Caesarea (SC) is a surgical procedure to deliver the fetus through an incision in the abdominal and uterine wall. Patients with a history of previous sectio caesarea frequently experience acute pain, risk of infection, and lack of knowledge regarding post-SC contraception, requiring comprehensive nursing care. Objective: To describe the application of nursing care in a patient with post-operative sectio caesarea with a history of sectio caesarea indication. Methods: This study used a descriptive method with a case study approach. Data were collected through interviews, observation, documentation, and relevant literature review. Results: Assessment of Ny. S revealed three nursing diagnoses: acute pain, knowledge deficit, and risk of infection. Interventions included pain management, family planning (KB) health education, and infection prevention through wound care. Following nursing interventions, the knowledge deficit resolved completely, while acute pain and risk of infection were partially resolved. Conclusion: Systematic nursing care can effectively address nursing problems in post-SC patients and improve patient health outcomes.